A Terpene Synthase Is Involved in the Synthesis of the Volatile Organic Compound Sodorifen of Serratia plymuthica 4Rx13 - Domik, Dajana; Thürmer, Andrea; Weise, Teresa; Brandt, Wolfgang; Daniel, Rolf; Piechulla, Birgit (Frontiers in Microbiology, 2016)
Bacteria release a plethora of volatile organic compounds (VOCs), including compounds with extraordinary structures. Sodorifen (IUPAC name: 1,2,4,5,6,7,8-heptamethyl-3-methylenebicyclo[3.2.1]oct-6-ene) is a recently identified and unusual volatile hydrocarbon that is emitted by the rhizobacterium Serratia plymuthica 4Rx13. Sodorifen comprises a bicyclic ring structure solely consisting of carbon and hydrogen atoms, where every carbon atom of the skeleton is substituted with either a methyl or a methylene group. This unusual feature of sodorifen made a prediction of its biosynthetic origin very difficult and so far its biosynthesis was unknown. To unravel the biosynthetic pathway we performed genome and transcriptome analyses to identify candidate genes. One knockout mutant (SOD_c20750) showed the desired negative sodorifen phenotype. Here it was shown for the first time that this gene is indispensable for the synthesis of sodorifen and strongly supports the hypothesis that sodorifen descends from the terpene metabolism. SOD_c20750 is the first bacterial terpene cyclase isolated from Serratia spp. and Enterobacteriales. Homology modeling revealed a 3D structure, which indicated a functional role of amino acids for intermediate cation stabilization (W325) and putative proton acceptance (Y331). Moreover, the size and hydrophobicity of the active site strongly indicated that indeed the enzyme may catalyze the unusual compound sodorifen.